Обучение иностранному языку и время - Михайловна Бразаускене, Елена (Slavistica Vilnensis, 2009)
This article reflects upon the textbook, ‘Lithuaniain Language for All’ (1992–1993), written by V. Chekmonas and I. Chekmoniene, which is still up-to-date. The novelty of this textbook lies in its approach to the teaching of the Lithuanian language as a speech activity rather than a system. The present task is to develop multilingual competence in a multicultural context. The Common European framework of reference for language learning, teaching and assessment represents the latest stage in a language teaching process. This document, as well as the European Language Portfolio, must be used in foreign-language teaching practices at the university level.